Impact of maternal nutritional literacy and feeding practices on the growth outcomes of children (6–23 months) in Gujranwala: a cross-sectional study - Tahreem, Aaiza; Rakha, Allah; Anwar, Rimsha; Rabail, Roshina; Maerescu, Cristina Maria; Socol, Claudia Terezia; Criste, Florin Leontin; Abdi, Gholamreza; Aadil, Rana Muhammad (Frontiers in Nutrition, 2025)
IntroductionMalnutrition contributes to approximately 45% of deaths among under 5 years children in low and middle-income countries. Poor maternal knowledge and failure to comply with recommended Infant and Young Child Feeding (IYCF) practices are known risk factors for malnutrition but there are inconsistencies in the literature. Therefore, this cross-sectional study of 100 mother–child pairs in district Gujranwala aimed to assess maternal nutritional literacy (MNL) and maternal feeding practices (MFP) and their ultimate impacts on child growth.MethodsA researcher administered questionnaire that was the combination of WHO model questionnaires and FAO Nutrition-related KAP model questionnaires was used to collect the data from mothers while and anthropometric measurements of children were taken by following the standard methods.ResultsResults showed that 57% of mothers had average nutritional knowledge and feeding practices were not satisfactory. Only 12% of mothers-initiated breastfeeding within the first hour of birth, 7% of infants were exclusively breastfed, while 27.27% continued to be breastfed beyond 1 year. Complementary foods were timely introduced to 53% of infants, 47% received minimum meal frequency and 34% met the minimum dietary diversity criteria. Additionally, the consumption of unhealthy foods, sugar-sweetened beverages, and zero consumption of fruits and vegetables was practiced by 71, 23, and 27% of infants and young children, respectively. Prevalence of stunting, wasting, underweight and overweight was 19, 9, 12, and 12%, respectively. A non-significant association was observed between MNL and MFP with growth outcomes with a few exceptions. The odds of being wasted (β = 1.903, OR = 6.706, p < 0.05) and underweight (β = 1.732, OR = 5.654, p < 0.05) are higher among children who had vaginal birth. Higher odds of being stunted (β = 2.173, OR = 8.788, p < 0.05) were observed among those whose mothers had middle school education compared to those having higher education.ConclusionOverall results indicated a dire need not only to create nutritional awareness among mothers in Gujranwala but also to provide a support system for mothers to help them implement standard feeding practices.